2021
DOI: 10.1016/j.curtheres.2021.100655
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitric Oxide in the Efficacy of Adenosine, Lidocaine, and Magnesium Treatment for Experimental Hemorrhagic Shock in Rats

Abstract: Background Nitric oxide (NO) plays multiple roles regulating the central nervous, cardiovascular, and immune systems. Objective Our aim was to investigate the role of NO in the efficacy of hypertonic saline (7.5% sodium chloride [NaCl]) adenosine, lidocaine, and magnesium (ALM) to improve mean arterial pressure (MAP) and heart rate following hemorrhagic shock. Methods One hundred one male Sprague-Dawley rats (mean [SD] weight = 425 [6] g) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…It is widely known that L-NAME increases MAP following hemorrhagic shock via its cardiac and arteriolar vasoconstrictive effects ( 50 ). We confirmed this MAP-raising effect in our saline controls in a rat hemorrhagic shock model where MAP increased from ~30 to ~60 mmHg following bolus administration of 7.5% NaCl + (L-NAME) [ Figure 3 ; ( 25 )]. The inability of ALM to resuscitate MAP in the presence of L-NAME indicates activation of one or more NO-producing pathways for its normal operation ( 25 ).…”
Section: Alm Resuscitation Survival and Stabilization Is Nitric Oxide...supporting
confidence: 70%
See 3 more Smart Citations
“…It is widely known that L-NAME increases MAP following hemorrhagic shock via its cardiac and arteriolar vasoconstrictive effects ( 50 ). We confirmed this MAP-raising effect in our saline controls in a rat hemorrhagic shock model where MAP increased from ~30 to ~60 mmHg following bolus administration of 7.5% NaCl + (L-NAME) [ Figure 3 ; ( 25 )]. The inability of ALM to resuscitate MAP in the presence of L-NAME indicates activation of one or more NO-producing pathways for its normal operation ( 25 ).…”
Section: Alm Resuscitation Survival and Stabilization Is Nitric Oxide...supporting
confidence: 70%
“…We confirmed this MAP-raising effect in our saline controls in a rat hemorrhagic shock model where MAP increased from ~30 to ~60 mmHg following bolus administration of 7.5% NaCl + (L-NAME) [ Figure 3 ; ( 25 )]. The inability of ALM to resuscitate MAP in the presence of L-NAME indicates activation of one or more NO-producing pathways for its normal operation ( 25 ). Two likely candidates for ALM-NO interactions are possible.…”
Section: Alm Resuscitation Survival and Stabilization Is Nitric Oxide...supporting
confidence: 70%
See 2 more Smart Citations
“…A recent study in a severe hemorrhagic shock animal model showed that the efficacy of 7.5% saline and ALM (adenosine, lidocaine, magnesium) for resuscitation was blocked by NOS inhibitors, which produced a rapid fall in mean arterial pressure (MAP), cardiovascular collapse, sustained ventricular arrhythmias and 100% mortality. The study concluded that the ability of 7.5% NaCl ALM to resuscitate appears to be linked to NO-enhancing pathway [74]. In human studies, the administration of NO by inhalation in patients with sepsis has been found safe [63].…”
Section: Safety Of Therapeutic Improvement Of No In Sepsismentioning
confidence: 99%